Analysis of Grouting Reinforcement Scope and Excavation Scheme for Shield Tunnel Link Passage - WANG Bo; WANG Yunzhou; CHEN Kai (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] During the construction of shield tunnel link passages using mining method, excessive soil collapse and land subsidence can pose significant safety risks. Since the scope of grouting reinforcement and the excavation scheme directly affect land subsidence and the safety of existing tunnels，it is necessary to analyze both the grouting reinforcement scope and the excavation strategy. [Method] Taking the link passage between Tanzikou Station and Dinggong Road South Station on Nanchang Rail Transit Line 4 as research object, the effects of different grouting reinforcement scopes and excavation partitions on tunnel excavation is simulated by PLAXIS 3D finite element software. The finite element simulation results are compared with actual monitoring data for validation. [Result & Conclusion] Partitioned excavation of link passage effectively reduces tunnel and passage deformation, as well as land subsidence. A larger grouting scope results in less deformation and subsidence; when the grouting reinforcement scope exceeds 3 meters, further increase in reinforcement thickness leads to only slight land subsidence reduction. A grouting reinforcement scope of 3 meters for link passage is both economically efficient and meets all safety and design requirements.